2011
DOI: 10.5194/nhess-11-1311-2011
|View full text |Cite
|
Sign up to set email alerts
|

Radon concentrations in abandoned mines, Cumbria, UK: safety implications for industrial archaeologists

Abstract: Abstract. This paper presents a number of surveys performed in a geographical area of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In many mines (Gillmore, Phillips, Denman, Sperrin, & Pearce, 2001), some caves (Sánchez, de la Torre Pérez, Sánchez, & Correa, 2013) and now in the Chernobyl object shelter (Ogorodnikov et al, 2009) (known commonly as the sarcophagus) high concentrations of radon and its radioactive daughters can be found. Gavin Gillmore at Kingston-upon Thames has suggested that industrial archaeologists should take care to avoid excessive radon exposure while working underground in places such as disused mines (Gillmore, Gharib, Denman, Phillips, & Bridge, 2011). While it should be clear that 222 Rn is formed by the alpha decay of 226 Ra present in the minerals in caves and mines, the 220 Rn (Thoron) at the Chernobyl site is due to the decay of the 224 Ra formed from the radioactive decay of 232 U.…”
Section: Charcoalmentioning
confidence: 99%
“…In many mines (Gillmore, Phillips, Denman, Sperrin, & Pearce, 2001), some caves (Sánchez, de la Torre Pérez, Sánchez, & Correa, 2013) and now in the Chernobyl object shelter (Ogorodnikov et al, 2009) (known commonly as the sarcophagus) high concentrations of radon and its radioactive daughters can be found. Gavin Gillmore at Kingston-upon Thames has suggested that industrial archaeologists should take care to avoid excessive radon exposure while working underground in places such as disused mines (Gillmore, Gharib, Denman, Phillips, & Bridge, 2011). While it should be clear that 222 Rn is formed by the alpha decay of 226 Ra present in the minerals in caves and mines, the 220 Rn (Thoron) at the Chernobyl site is due to the decay of the 224 Ra formed from the radioactive decay of 232 U.…”
Section: Charcoalmentioning
confidence: 99%